Active Athletes' Perceptions of Career and Education Services in the United Kingdom - North, Julian; Lavalee, David (My University, 2003)
This study examined perceptions of career and education services among a sample of active athletes in the United Kingdom. Employing both qualitativeand quantitativemethodologies, athletes eligible to receive support services through the United Kingdom Athlete Career and Education Program (ACE UK) were assessed in terms of their views of athlete advisers and ACE UK services. This research utilized a two-stage methodology. Stage one was qualitativein nature and involved nine face-to-face interviews with athletes drawn from the ACE UK program database. These interviews were used to develop a grounded understanding of the language used and the key issues experienced by the athletes. Stage two was a self-administered postal survey. The aim of this stage was to examine the extent to which the issues and themes generated in the first stage were shared by the wider ACE UK athlete population. The questionnaire employed in stage two was four pages long and consisted primarily of closed questions focusing on topics developed by examining the key issues emerging from the first stage transcripts. These included athletes' education and career profiles, short term plans, long-term plans related to retirement from competitive sport (including expected years until career termination), and plans about life after sport. Some open-ended questions were also included to allow the athletes to expand on their experiences of, and opinions on, the ACE UK program. A total of 561 valid and completed questionnaires were returned by the athletes (response rate=57%). There were slightly more males (54%) than females (46%) in the sample, and more able-bodied athletes (83%) than athletes with disabilities (17%). The average age of the overall sample was 26.0 years old. A total of 37 individual and team sports were represented. Service provision is coordinated through an 'athlete adviser' - ACE UK athlete advisers are typically ex-athletes who have received training in the provision of career and education services, but primarily have been recruited because of their understanding of the needs of elite athletes. Results revealed that athletes perceived advisors as central to their career and education service provision, and that this accounted predominantly for its success. The adviser's role as a friend, mentor, and motivator was found to be as significant as the adviser being a source of information and advice, as well as a conduit to other more specialized services. Although a large proportion of athletes were aware of and were using ACE UK services, the reasons for not participating included a lack of perceived need, lack of awareness, athletes' time constraints, and access difficulties.
Keywords: academic support; student development; UK; career development